The complete guide to ABC's molecular biology certification exam - Roy, Tiffany; Price, Tatum (Boca Raton : CRC Press, 2020)
"In 2009, the National Academy of Sciences (NAS) authored the report Strengthening Forensic Science in the United States: A Path Forward. In it, the Committee expressed the need for accreditation and certification. Accreditation, long recognized by public labs as an important benchmark in quality, was recognized as an important way to standardize laboratories that provide forensic services. Certification can play an important role as a method of oversight in the forensic sciences-something also recommended by the - National Commission on Forensic Science in October 2014. The Complete Guide to the ABC's Molecular Biology is a professional certification examination preparation text for forensic scientists taking the American Board of Criminalistics Examination in Molecular Biology. The book serves as a resource for forensic scientists-who are facing more and more pressure to become certified-to support them in their pursuit of forensic certification. In the years since the NAS report was published, there has been increased discussion of forensic certification requirements. ABC's Molecular Biology exam is a quality certification, and learning the concepts for it will invariably help any professional working in the field. The book prepares readers in all relevant topic areas, including: accreditation, safety, biological screen principles, anatomy and cell biology, crime scene and evidence handling, concepts in genetics, biochemistry, statistics, DNA evidence, and DNA testing. The book will be particularly helpful for forensic science laboratory technicians, police and investigations professionals, forensic serology and DNA analysts, attorneys, and forensic science students. This study guide follows the guidelines for the exam and presents all the information necessary to prepare individuals to pass the exam"--
OCLC-licensed vendor bibliographic record.
Keywords: Forensic scientists -- Certification -- United States -- Study guides; Molecular biology -- Examinations -- Study guides; LAW / Forensic Science; SCIENCE / Life Sciences / Genetics & Genomics; SCIENCE / Life Sciences / Biology / Molecular Biology